H-PMI : uma Arquitetura de Gerenciamentos de Privilégios para Sistemas de Informação da Área de Saúde - Custódio, Igor Vitório (2010)
The use of Information Systems in health environments, like the substitution of paper versions of medical records by electronics ones, has improved patient assistance and allowed such information to be available in a more accessible way. Along with this technology, however, there are significant issues raised by the patients about the access control over their confidential data, which becomes more available and could be accessed by unauthorized people. It is in this scenario that Health - Privilege Management Infrastructure, or H-PMI, is presented in this work. It aims to provide a software architecture for privilege management in health environments. H-PMI aims to be adherent to the Brazilian laws and rules related to the access to electronic medical records, like the ones defined in Manual de Certificação de Sistemas da Área de Saúde by Conselho Federal de Medicina and Sociedade Brasileira de Informática em Saúde. The main objective of this work is to specify the envisioned H-PMI, so it can provide restricted access to electronic medical records in accordance with the appropriate law and recommendations security guarantees, allowing trusted access to sensitive data while allowing circumstantial access to these data in exceptional situations. In order to evaluate the applicability of the proposed H-PMI architecture we have developed the Web H-PMI, which is integrated with the Google Health platform. The obtained results show that the developed architecture can be applied in existing health environments.